Modification in Structural, Morphological, Magnetic and Ferroelectric Properties of Calcium-Doped Bismuth Ferrite Nanoparticles (Journal of Engineering Science, 2020)
The structural, morphological, magnetic and ferroelectric properties of calcium (Ca) doped bismuth ferrite (BFO) synthesized using a sol-gel method were studied. X-ray diffraction (XRD) analysis followed by Rietveld refinement revealed the lattice distortion of BFO after doping with 6% and 8% Ca. This also led to the reduction in particle size by creating oxygen vacancies, which was observed from the surface morphology using Field Emission Scanning Electron Microscopy (FESEM). The Magnetic properties exhibited some enhancements in saturation magnetization when the particle size was near a limiting value. The reduction in the coercive magnetic field with the increase in dopant concentration was also evident from the M-H hysteresis loop measured by Vibrating Sample Magnetometer (VSM). The Ferroelectric P-E hysteresis loop exhibited an increased symmetry in the hysteresis loop and increase in the polarization with the increase in %Ca. The 8% Ca doped BFO exhibited an incomplete saturation in the hysteresis loop and was evident to exhibit leakage current characteristics.Journal of Engineering Science 11(1), 2020, 123-131